Stabilitas fisik dan uji iritasi produk peel-off mask dari ekstrak H. scabra, A. marina, dan bittern: Physical stability and irritation peel-off mask products from H. scabra, A. Marina extracts, and bittern - Ridyawati, Ika Wahyu; Asih, Eka Nurrahema Ning (Jurnal Pengolahan Hasil Perikanan Indonesia, 2024)
A peel-off mask is a type of cosmetic that is widely used for treating dry facial skin. This product can moisturize and provide a relaxing effect because it is rich in minerals in the skin. Mineral-rich marine biota that have potential as ingredients for peel-off masks include extracts of Holothuroidea scabra, Avicennia marina, and bittern. The aim of this study was to determine the best peel-off mask product formula from H. scabra, A. marina, and bittern extracts, based on physical stability and irritation tests. The tests included extract yield, peel-off mask formulation, physical stability (organoleptic, cycling test, pH test, and drying time test), and irritation (eritema, hot, and itchy rash) tests. The formula used in this study is bittern (mL)+H. scabra (mg)+A. marina (mg), with F0 (control), F1 (33.33+33.33+33.33), F2 (50+25+25), F3 (25+50+25), and F4 (25+25+50). The research results show that the best physical stability of the product is found in F2. (bittern 50 mL, 25 g H. scabra extract 25 g, and A. marina). This formula is safe to use on facial skin because 30 panelists did not experience irritation (erythema, heat, and itching) with a product pH of 5.52 according to the normal skin value on the face.